2013
DOI: 10.1002/2013eo500001
|View full text |Cite
|
Sign up to set email alerts
|

Flooding the Colorado River Delta: A Landscape‐Scale Experiment

Abstract: A large pulse of water is planned to be released into the dry Colorado River channel in Mexico. This engineered experimental spring flood, which will flow from Lake Mead and pass through downstream reservoirs, is the culmination of decades of applied research. The pulse flow is a rare opportunity for research at the landscape scale [Glenn et al., 2013].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 8 publications
0
17
0
2
Order By: Relevance
“…The role of lateral groundwater flow in watershed dynamics has been demonstrated in prior studies (e.g., Sear et al ; Brouyère et al ; Kollet and Maxwell ; Decharme et al ; Flessa et al ; Miller et al ; Fang and Pomeroy 2016; Buto et al ). On a large‐scale, Condon and Maxwell () and Condon et al () demonstrated the close connections between lateral groundwater flow streamflow and evapotranspiration (ET) using an integrated groundwater surface water model.…”
Section: Introductionmentioning
confidence: 67%
“…The role of lateral groundwater flow in watershed dynamics has been demonstrated in prior studies (e.g., Sear et al ; Brouyère et al ; Kollet and Maxwell ; Decharme et al ; Flessa et al ; Miller et al ; Fang and Pomeroy 2016; Buto et al ). On a large‐scale, Condon and Maxwell () and Condon et al () demonstrated the close connections between lateral groundwater flow streamflow and evapotranspiration (ET) using an integrated groundwater surface water model.…”
Section: Introductionmentioning
confidence: 67%
“…These impacts include the functional extinction of a key bivalve species and suppressed growth rates in the iconic fish Totoaba macdonaldi, among other faunal effects, and yielded the first science-based estimates of the water flow across the US-Mexico border that will be needed to restore some modicum of marine ecosystem services (Zamora-Arroyo & Flessa 2009). Indeed, these assessments of environmental needs, along with estimates of flows required to sustain riparian habitats (Zamora-Arroyo et al 2005), played an integral role in a newly signed international agreement to provide water for the delta's environments (Flessa et al 2013). …”
Section: Documenting Shifting Baselinesmentioning
confidence: 99%
“…For example, the Australian Murray-Darling Basin Plan, designed to re-allocate water from cropland to riparian and riverine ecosystems, was unpopular with many farmers and only feasible because of the extreme dysfunction of the river system and the political will of the central government, yet is still unlikely to provide sufficient water to sustain riparian habitats under projected future climate change (Kirby et al, 2014;Wheeler et al, 2014). Likewise, existing water laws make changes to water management in water-stressed southwestern North America challenging (Palmer et al, 2009;Sabo et al, 2010), although experimental flows have been implemented on some rivers (Patten et al, 2001;Shafroth et al, 2010;Flessa et al, 2013). Climate change may further reduce the feasibility of adjusting water management operations for riparian restoration, especially in regions where warmer temperatures increase water demand and reduce supply (e.g.…”
Section: Water Managementmentioning
confidence: 99%